The Antecedents and Consequences of Individual Adaptive Performance: A Systematic Literature Study - Nandini, Widya; Gustomo, Aurik; Sushandoyo, Dedy (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2022)
The emergence of industry 4.0 and the dynamic changes in the market have urged organizations to be more agile. An organization demands that its employees have a high adaptive performance to be agile. Existing research on individual adaptive performance, however, emerges from various contexts, including the context of an employee’s develop-ment process and organizational capabilities. Thus, a systematic literature study to identify the topics addressed in the existing studies and the research gap as the foundation for future research direction is scarce and needed. This study analyzes fifty-nine highly relevant papers based on the topics and research approaches/methods. From the analysis, it is found that learning and training strategies are the topics that are less investigated; therefore, such issues are suggested to be conducted in future studies to fill the knowledge gap.Moreover, it is also proposed in this paper a conceptual model that is built based on learning and training strategies. The model can be used to enhance our understanding of the mechanism of individual adaptive performance. Regarding the research approach, it is found in this study that much of the existing research employed a quantitative research approach. Therefore, it is suggested that future research use other research approaches, including a mixed-method approach. Such an ap-proach is argued powerfully in delivering the result of a study that is both thorough and broad in addressing the top-ic of the mechanism of individual adaptive performance.